2022
DOI: 10.3390/tomography8010041
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pneumonia and Lung Cancer: A Challenge for the Radiologist Review of the Main Radiological Features, Differential Diagnosis and Overlapping Pathologies

Abstract: The COVID-19 pneumonia pandemic represents the most severe health emergency of the 21st century and has been monopolizing health systems’ economic and human resources world-wide. Cancer patients have been suffering from the health systems’ COVID-19 priority management with evidence of late diagnosis leading to patients’ poor prognosis and late medical treatment. The radiologist plays a pivotal role as CT represents a non-invasive radiological technique which may help to identify possible overlap and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…In the initial phases of the pandemic, the accessibility to diagnostic and therapeutic pathways was impaired due to the conversion of several departments into COVID-19 units, causing disruptions to oncological screening, treatment, and surveillance [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Additionally, COVID-19 infection can cause serious complications in oncological patients undergoing chemotherapy or recovering from recent surgery [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the initial phases of the pandemic, the accessibility to diagnostic and therapeutic pathways was impaired due to the conversion of several departments into COVID-19 units, causing disruptions to oncological screening, treatment, and surveillance [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Additionally, COVID-19 infection can cause serious complications in oncological patients undergoing chemotherapy or recovering from recent surgery [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since CT can detect small areas of GGO (23), it is a promising imaging tool for longitudinal monitoring of the disease. Several studies have applied serial CT to assess the evolution of the COVID-19 lesions during the disease (24)(25)(26). Only qualitative evaluation was performed, e.g., by using a scoring system of 0-5 in each of 5 lobes in the lung, with a total score of 0-25.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with lung cancer coexisting with TB infection usually present with cough, expectoration, and other non-specific symptoms, such as fever and weight loss, which are easily confused with the manifestations of cancer itself and pneumonia of other etiologies. 16,25,26 Our results showed that new consolidation, patchy opacity/nodules, or tree-in-bud sign is manifested in chest computed tomography (CT) or Xray imaging for patients with lung cancer coexisting with TB infection during ICI treatment. Therefore, if new radiological lesions appear in patients with lung cancer during ICI treatment, the nature of the lesions should be clarified.…”
Section: Discussionmentioning
confidence: 77%